Study on Synthesis and Characterization of New 8-Trifluloromethyl Quinazolin-2,4-(3H)-Dione Nucleosides - Break, Laila M. (Current Advances in Chemistry and Biochemistry Vol. 8, 2021)
Synthesis of 8-trifluloromethyl quinazolin-2,4-(1H,3H)-dione 2. which have been ribosylated by coupling with 1-O-acetyl-2,3,5-tri-O-benzoyl- -D-ribofuranose 4 by using the silylation method, afforded mixture b-and a-anomeric of the benzoylated nucleoside derivatives 5 and 6, respectively. In this review, quinazolin-2,4-(3H)-dione nucleosides containing trifluloromethyl group were designed as part of our continuing interest in the synthesis of new nucleosides as expected their biological activity. Debenzoylation of each of 5 and 6 by sodium metal in dry methanol to afford the corresponding free nucleosides 7 and 8 respectively. The structures of the newly synthesis compounds have been confirmed on the basis of elemental analyses, IR, 1HNMR, 13CNMR and Mass spectral data.